School leadership in Latin America 2000–2016. (March 2018) - Flessa, Joseph; Bramwell, Daniela; Fernandez, Magdalena; Weinstein, José
School site leadership has commanded the attention of researchers and policymakers in Anglo-American jurisdictions for at least two decades, but little is known about how many other parts of the globe have addressed this topic. This paper reviews published research and policy documents related to school leadership in Latin America between 2000–2016. Applying rapid mapping techniques used for scoping studies, we review 359 research and policy documents and give 'coherent, meaningful shape' to what we know and what we don't know about school leadership in the region. Attention in research and policy to school leadership in Latin America was relatively slow to arrive: whilst it grew steadily in the first decade of this century it remains low compared to other regions of the world. We provide an overview of the school leadership policy environment in several countries, describing recruitment, selection, evaluation, and job responsibilities of principals; relevant leadership frameworks; and requirements for training or professional development. We speculate on what might explain the diverse ways that school leadership has been taken up in the region: degree of school system centralization; policy borrowing; stage of development; technocratic problem solving; and neoliberal accountability.